Pengaruh Media Sosial dan Kepercayaan Terhadap Keputusan Pembelian Produk Pada Yuikaa Shop Bima - Jihan Fahirah Humairah; Intisari Haryanti (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2021)
This study aims to determine the direct effect of social media and trust on product purchasing decisions at Yuikaa Shop Bima. This research method using quantitative methods. The sample used in this study was purposive sampling, the total of 100 respondents who had bought Yuikaa Shop Bima products. The analysis technique used is multiple linear analysis to determine how much influence the independent variables have on the dependent variable collectively and to find out how much influence the independent variables have on the dependent variable individually. Based on the results of this study, it shows that social media and trust have a significant effect on purchasing decisions at Yuikaa Shop Bima either partially or simultaneously.